Occurrence of toxic saponins in drinks - Souza, Amaro Henrique de (Pesquisa Agropecuaria Brasileira, 2014)
The author confirmed the existence of strong concentrations of saponin in time English product named "Foamine", that has been sold for the last 30 years in Brazilian markets as "Liquorice Extract". The first investigations were conducted in the National Analytical Laboratory of the Brazilian Government by chemists, Raquel Nifhier and Dinah Viana Feijó. In comparative essays of the hemolytic index the author found that although time genuine extracts of liquorice (Glycyrrhiza glara L.) are toxic foaming drugs, they do not cause sheep or human red blood hemolysis. Nevertheless, "Foamine" produced hemolytic activity similar to extracts of "panamá" (Quillaja saponaria Molina), "juazeiro" (Ziziphus joazeiro M.) and "salsaparrilha" (Smilax officinalis Kunth) with hemolysis occurring at ratios of ten parts per million. The author reviews the physical essays for determination of saponines, emphasizing however physiological methods such as the hemolytic index. Besides a general table showing the results of the experiments, the result of several other workers, in saponines, are tabulated. Thirty five bibliographic references are cited.